Optimized guidelines for feminized seed production in high-THC Cannabis cultivars - Timoteo Junior, Antonio A.; Oswald, Iain W. H. (Frontiers in Plant Science, 2024)
With the partial legalization of high-THC Cannabis sativa across 23 states for recreational use and 38 states for medical purposes in the United States, the Cannabis industry is poised for significant growth. Projected to reach a sales volume of $50.7 billion by 2028, this growth is driven by the trend of lifting Cannabis prohibition. High-THC C. sativa cultivars, containing more than 0.3% delta-9 tetrahydrocannabinol (Δ9-THC) as defined by the 2018 US Farm Bill, are used for both medicinal and recreational purposes. Cannabis sativa is a short day, dioecious, annual plant, where female plants are favored for THC production, which requires seed feminization techniques to ensure an accurate female plant population. This involves using an ethylene inhibitor to induce sex reversal, leading to male flower development on female plants, allowing for self-pollination and the production of feminized seeds. However, challenges such as seed viability and the occurrence of male flowers in progeny have been noted. This review provides guidelines to enhance the production of viable feminized seeds in high-THC Cannabis cultivars. Literature findings indicate that Silver Thiosulfate (STS) is the most effective ethylene inhibitor for sex reversal and seed feminization in high-THC Cannabis cultivars. Specifically, a single dose of 3 mM STS should be applied during the vegetative stage via foliar spraying until runoff, followed by exposure to a short photoperiod of up to 12 hours to induce flowering and seed production. Progeny plants should be assessed for seed germination rate and compared for growth performance with the original parent plant to assess the declining effects of inbreeding. Adhering to these guidelines can improve the quality and viability of feminized seeds, meeting commercial market standards and industry demands for high-THC Cannabis cultivars.